Microglia in action: how aging and injury can change the brain’s guardians - Lourbopoulos, Athanasios; Ertürk, Ali; Hellal, Farida (Frontiers in Cellular Neuroscience, 2015)
Neuroinflammation, the inflammatory response in the CNS, is a major determinant of neuronal function and survival during ageing and disease progression. Microglia, as the resident tissue-macrophages of the brain, provide constant support to surrounding neurons in healthy brain. Upon any stress signal (such as trauma, ischemia, inflammation) they are one of the first cells to react. Local and/or peripheral signals determine microglia stress response, which can vary within a continuum of states from beneficial to detrimental for neuronal survival, and can be shaped by ageing and previous insults. In this review, we discuss the roles of microglia upon an ischemic or traumatic injury, and give our perspective how ageing may contribute to microglia behavior in the injured brain. We speculate that a deeper understanding of specific microglia identities will pave the way to develop more potent therapeutics to treat the diseases of ageing brain.